2012
DOI: 10.1002/j.0022-0337.2012.76.4.tb05280.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental Students and Bloodborne Pathogens: Occupational Exposures, Knowledge, and Attitudes

Abstract: Dental professionals may be exposed to bloodborne pathogens in their work, and dental students may be a particularly vulnerable group. Fear of exposure has also been linked to discriminatory practices. A cross-sectional survey of dental students was conducted at one U.S. dental school to assess their knowledge about the transmission of bloodborne pathogens and management of exposures; the frequency of their bloodborne pathogen exposures (BBPEs); and associations among their prior exposure, knowledge, perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 15 publications
5
56
5
Order By: Relevance
“…Unlike this research, studies that investigated the knowledge of dental students about HIV / AIDS [25][26][27] and occupational of blood-borne pathogens [28,29] showed that knowledge about some aspects was greater among students with higher educational level. Keser et al [25] justi ed this nding by the fact that the older group may have gained more experience over the years and was exposed to larger number of patients compared to the younger group.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Unlike this research, studies that investigated the knowledge of dental students about HIV / AIDS [25][26][27] and occupational of blood-borne pathogens [28,29] showed that knowledge about some aspects was greater among students with higher educational level. Keser et al [25] justi ed this nding by the fact that the older group may have gained more experience over the years and was exposed to larger number of patients compared to the younger group.…”
Section: Discussioncontrasting
confidence: 57%
“…A fact that attracted attention was that studies on knowledge about the transmission of blood-borne pathogens among dental students conducted by Myers et al [28] and Brailo et al [29], published in 2012 and 2011, respectively, did not address syphilis. The study by Wu et al [15], published in 2016, included the disease, probably due to its increasing prevalence worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Evidence to date suggests that the greater proportion of sharps injuries occur as a result of inappropriate handling and disposal of instruments. 6,18,19 In addition, few studies have explored the attitudes and beliefs of primary dental care practitioners towards reporting occupational exposures in primary dental care. Given this combination of factors the aim of the study was to evaluate dentists' current reporting behaviour as well as their beliefs about reporting occupational exposures to blood and other oral fluids in Scottish dental practices.…”
Section: Aimsmentioning
confidence: 99%
“…Infection control recommendations for dentistry were first published by the Centers for Disease Control and Prevention (CDC) in 1986, 1 last updated in 2003, 2 and have been widely disseminated to practicing dentists, dental educators, and state Boards of Dental Examiners. 3 Compliance with infection control protocols in dental practice has been variable at best, both in the United States 3,4 and in developing countries. 5 Compliance in a school environment has also been less than ideal, 6 and 1 study suggested a decrease over time for some parameters.…”
mentioning
confidence: 99%